A study on the electrical insulating properties of the epoxy resin - Mohamed Afendi Mohamed Piah, author (Glasgow : University of Strathclyde, 1990)
This thesis summarizes the important physical and electrical characteristic of the epoxy resin and as a useful insulating material. Factors of chemical structure with influence the resulting resin properties are discussed and also a range of application of these resins is mentioned briefly. The breakdown mechanisms in the solid dielectric insulation have been reviewed. Diagostic testing which has been used when measuring the electrical properties of the epoxy resin in discussed. To establish the electrical properties of the epoxy resin, a series of experiments which provide information about the conduction mechanism and the glass transition temperature werecarried out. Finally the results of an experimental investigation of the effect of temperatureand frequency of applied voltage to the dielectric loss in an epoxy resin are presented. It is shown that the temperature, moisture and frequency have a great influence to the conduction of the polymers. Generally it is cleared that the electrical, physical and chemical properties of the epoxy resin areall stem from the basic molecular structure of the Polymerised resin.